2005
DOI: 10.1007/s00701-005-0608-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermography – a valuable tool to test hydrocephalus shunt patency

Abstract: Infrared-thermography is a valuable and promising tool for replacing CCT-scanning as a screening method to test shunt function in hydrocephalic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Goetz et al used IRT to monitor hydrocephalus shunt patency, using cold challenge testing to assess temperature differentials, while Zurek et al used IRT to monitor tissue perfusion in a study involving a novel treatment for cerebral palsy. 33 34 An innovative study by Coben et al used IRT to record the temperature change in a specific area of the head (named ‘Fpz’), lying over a region of the brain implicated in attention-deficit/hyperactivity disorder. Using the temperature differential to detect patients with disease, a sensitivity of 66% was reported and Coben et al suggested that IRT was superior to the limited alternative diagnostic tests for the disease.…”
Section: Irt In Childrenmentioning
confidence: 99%
“…Goetz et al used IRT to monitor hydrocephalus shunt patency, using cold challenge testing to assess temperature differentials, while Zurek et al used IRT to monitor tissue perfusion in a study involving a novel treatment for cerebral palsy. 33 34 An innovative study by Coben et al used IRT to record the temperature change in a specific area of the head (named ‘Fpz’), lying over a region of the brain implicated in attention-deficit/hyperactivity disorder. Using the temperature differential to detect patients with disease, a sensitivity of 66% was reported and Coben et al suggested that IRT was superior to the limited alternative diagnostic tests for the disease.…”
Section: Irt In Childrenmentioning
confidence: 99%
“…Because infrared cameras are compact, lightweight and accurate, these devices allow for rapid temperature measurement of a large number of people without exposure to potential contagious diseases. Researchers have used thermography to diagnose thyroid diseases (Helmy et al, 2008), confirm hydrocephalus shunt patency (Goetz, Foertsch, Schoenberger, & Uhl, 2005), examine diabetes wound management (Bharara et al, 2006) and diagnose and treat leg ulcers (Mercer et al, 2008). Researchers are using infrared thermography in the area of exercise physiology to map out temperature differentials during exercise and rest (Merla, Mattei, Di Donato, & Romani, 2010).…”
Section: Human Research Using Infrared Thermographymentioning
confidence: 99%
“…Surveillance for hypothermia or hyperthermia of all infants from a distance using infrared temperature measurement of their forehead is possible, especially in a delivery room situation. Thermography has been used to assess shunt patency which could be employed in the NICU (Goetz, Foertsch, Schoenberger & Uhl, 2005). Researchers have shown that infrared thermography can be used to study temperature profiles of infants on warming tables, especially for a global picture of body temperature in the delivery room (Christidis et al, 2003).…”
Section: 4 Discussionmentioning
confidence: 99%